IMPACT OF TRANSFER OF AGRICULTURAL LAND TO NON AGRICULTURAL LAND ON FARMERS IN GAMBUT DISTRICT, BANJAR REGENCY - Muhammad Sofia Azhar (Universitas Lambung Mangkurat, 2022)
The increase in population and economic needs in Banjar District, to be precise, the Peat District, has an effect on the increasing land needs for community activities. This is one of the driving forces for the conversion of agricultural land to non-agricultural land. On the other hand, the increasing need for food has made the government have to establish a policy to protect food agricultural land so that it is not converted. Efforts to control the change in the function of food land need to look at the factors that affect land use change in each region. Thus, the established program is more effective because it is able to answer the problems faced by the community, especially land owners. This study aims to determine the factors of land change and the impact of the change in function from agricultural to non-agricultural land for farmers. This research method uses qualitative methods through collecting data through the stages of observation, data reduction, data presentation, and drawing conclusions. As well as interviews. The results of the study in the factor of land conversion for farmers due to government policies and economic pressure that occurred in family life. The impact of land use change in the Peat District that is felt by the farmers is the narrow land for cultivation and flooding that cannot be calculated when the water rises